Phenotypic diversity in experimental hepatomas: the concept of partially blocked ontogeny. The 10th Walter Hubert Lecture. - Potter, V. R. (Nature Publishing Group, 1978)
Cancer cells should be seen not as exclusively a problem in cell proliferation, but rather as a problem combining the processes of proliferation and differentiation, hence the phrase introduced in 1968: "oncogeny is blocked ontogeny". Cancer tissues resemble foetal tissues in many ways but they differ from foetal tissue in being unable to "recapitulate the total programme leading to an orchestrated collection of organism-serving cells" that are programmed "to make the organ as adaptive as possible to the range of environmental variations in which it evolved". Citing the "Osgood Principle" from the 1950's, recent supporting evidence was described, in which the most mature differentiated cells exert positive and negative feedback upon the proliferation of their progenitor stem cells. Advanced examples in the haemopoietic series were drawn from the work of Sachs, Metcalf, Till and McCulloch, and Kurland and Moore. The blocked ontogeny hypothesis was further elaborated in the concept of "partially-blocked ontogeny", which is intended to describe a situation in which highly differentiated slowly growing tumours contain some cells which have left the proliferating pool to differentiate along the normal pathway, but are blocked somewhere short of the final organism-serving state, in harmony with earlier suggestions by Osgood, by Pierce, and by Sachs.